Peran Aliansi Masyarakat Adat Nusantara dalam Mendukung Implementasi United Nations Declaration on the Rights of Indigenous Peoples di Indonesia - Alyanada, Ambar; Iskandar, Irwan (Journal of International and Local Studies, 2023)
Indigenous peoples have come to international attention marked by the approval of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) in September 2007. The declaration was supported by 144 countries, including Indonesia. In Indonesia, UNDRIP is needed as one of the policy bases in the regulation of indigenous peoples.  In its implementation, non-governmental organizations in the form of Non-governmental Organizations (NGOs) were also given the opportunity to play a role, and one of these NGOs was the Aliansi Masyarakat Adat Nusantara (AMAN). Thus, this paper analyses the role of AMAN in implementing UNDRIP. For this purpose, this paper uses the theory of non-governmental organization by David Lewis. The research method used qualitative method is descriptive with data collection techniques based on interview and analysis from journals, books, internet sites, newspapers and official documents. The result of this paper shows that the role of AMAN is included in 3 categories of NGO roles based on the theory proposed by David Lewis, namely Implementer, Catalyst and Partners.